Peningkatan Kemampuan Berpidato Berbahasa Inggris Siswa SMK Di Kabupaten Tegal - Firmansyah, Mochammad Sofyan; Alfian, Mohammad (Universitas Nusantara PGRI Kediri, 2022)
The ability to communicate using words or speaking is an ability that must be mastered by students in this millennium era. One of the ways to improve this speaking skill is through learning activities in the classroom. However, online learning that was implemented during the COVID19 pandemic has reduced students' opportunities and enthusiasm to learn how speak well through practicing with teachers. The purpose of holding this Community Service is to be able to improve and provide more knowledge to students, especially high school students (SMK) about how to speak, especially speaking in English. This service method is carried out through intensive question and answer to find out the obstacles and obstacles felt by students in speaking or making speeches in English. This online community service was attended by 40 participants from various backgrounds, both students (students and students) and teachers (lecturers and teachers). Many participants began to dare to speak both to ask questions and to express their opinions. From the implementation of this community service, it can be seen that students need face-to-face learning activities where they can talk/communicate directly to their teachers and friends without going through media intermediaries such as online learning activities today.